Islamic finance risk analysis and climate change - Al-Shaghdari, Fahd Mohammed Obad; Sharofiddin, Ashurov; Zakariyah, Habeebullah (Routledge (Taylor & Francis Group), 2025)
The chapter explores the convergence of Islamic finance and climate change by analysing how Islamic financial institutions can effectively manage climate-related risks through ethical investment practices. It aims to highlight innovative financial instruments and strategies that promote sustainable development, and assess their role in funding climate change mitigation and adaptation projects. The findings conclude the significant role of Islamic finance in combating climate change and the integration of ethical principles aligned with sustainable development objectives, alongside the deployment of innovative Shariah-compliant financial products, such as green Sukuk. The findings also reveal how customized risk management strategies are employed to consider environmental consequences.